The 8th International Conference on Software, Knowledge, Information Management and Applications (SKIMA 2014) 2014
DOI: 10.1109/skima.2014.7083530
|View full text |Cite
|
Sign up to set email alerts
|

Simulation analysis on effectiveness of nonlinear ultrasound imaging using synthetic cyst phantoms

Abstract: Application of nonlinear ultrasound techniques is recently gaining importance in medical imaging. Ultrasound imaging is a commonly used diagnostic method due to its low cost, safe and portable facilities. However, linear ultrasound imaging provides poor resolutions. The harmonic content can provide better resolution rather than the fundamental frequency. Conversely, increasing complexity is obvious impact of nonlinearity consideration.This simulation study presents a comparative analysis of linear and non-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A comparable upsurge in research projects utilising nonlinear analysis is observed in the field of communication engineering. [11] research sheds light on the use of nonlinear approaches in creating reliable communication systems that can withstand noise and signal distortions. Their work demonstrates how nonlinear equalisation techniques greatly improve the effectiveness and dependability of contemporary communication networks, setting the stage for systems that are more resistant to interference.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A comparable upsurge in research projects utilising nonlinear analysis is observed in the field of communication engineering. [11] research sheds light on the use of nonlinear approaches in creating reliable communication systems that can withstand noise and signal distortions. Their work demonstrates how nonlinear equalisation techniques greatly improve the effectiveness and dependability of contemporary communication networks, setting the stage for systems that are more resistant to interference.…”
Section: Literature Reviewmentioning
confidence: 99%